Make the Liberal Party great again - Ruddick, John (Melbourne, Vic. : Wilkinson Publishing, 2018)
A manifesto for Liberal Party supporters around Australia. In this timely book, John Ruddick calls for the Liberal Party of Australia to be brought not so much into the 21st century but rather into the latter part of the 20th century. The principal parties in almost all comparative democracies have in the last century become significantly more open, transparent and democratic than either of Australia's principal parties. Ruddick has been at the forefront of democratic reform within the Liberal Party for three decades. Make the Liberal Party Great Again is the culmination of his efforts and a call to arms. The book argues the Liberal Party should abandon the conflicted party room ballot to select the Liberal Party candidate for prime minister and introduce historic democratic reform that will invite all paid up Liberal Party members to have a vote on the most consequential decision the party makes. It's far from radical ... it’s actually the Westminster norm in the 21st century.
Includes bibliographical references.
Keywords: Liberal Party of Australia; Political parties -- Australia; Political leadership -- Australia; Politics & government; Australia -- Politics and government; Australian history; Australian